Diphtheria Incidence is a Public Health Challenge in Low- and Middle-Income Countries (LMICs) - Monica Dwi Hartanti; Novaria Sari Dewi Panjaitan; Syarif Hidayat; Fitriana Fitriana; Sunarno Sunarno; Sri Susanty (Public Health of Indonesia)
Background: Diphtheria remains a persistent public health issue, especially in low- and middle-income countries (LMICs), where vaccination coverage is often inadequate. Recent outbreaks, such as those in the 1990s, highlight the ongoing threat posed by this vaccine-preventable disease. The World Health Organization (WHO) provides data for monitoring the global trends in diphtheria cases, helping countries remain vigilant against its resurgence.